GOOGLE WORKSPACE MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - VIVIN AGUSTIN ANGGRAINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research is a qualitative research that aims to determine the improvement of mathematics learning outcomes by utilizing features in Google Workspace. The method in this research is carried out through two stages, the first is the preparation stage and the second is the implementation stage. The preparation stage is the teacher prepares lesson plans, classes and lesson topics on Google Classroom and schedules on Google Calendar. Then the teacher also prepares material on Google Slieds, pretest and posttest questions along with answer keys and points or scores on Google Forms whose results can be seen in Google Sheets. At the implementation stage, the teacher starts the class by greeting students in Google Classroom and starts a virtual face-to-face discussion with students using Google Meet by discussing learning materials. From the results of this study, it can be seen that there is an increase in students' mathematics learning outcomes in the pretest score before using Google Workspace with the posttest score after using Google Workspace. Google Workspace can also realize digital-based learning, students are more interested because they can learn wherever and whenever they are. Teachers are also easier in delivering all information and storing learning documents. ABSTRAKPenelitian ini merupakan penelitian kualitatif yang bertujuan untuk mengetahui peningkatan hasil belajar matematika dengan memanfaatkan fitur-fitur di Google Workspace. Metode dalam penelitian ini yaitu dilakukan melalui dua tahapan, yang pertama tahap persiapan dan yang kedua tahap pelaksanaan. Tahap persiapan yaitu guru mempersiapkan RPP, kelas dan topik pelajaran pada Google Classroom dan jadwal di Google Calender. Kemudian guru juga mempersiapkan materi di Google Slieds, soal pretest dan posttest beserta kunci jawaban dan poin atau nilai pada Google Form yang hasilnya dapat dilihat di Google Sheets. Pada tahap pelaksanaan, guru memulai kelas dengan menyapa peserta didik di Google Classroom dan memulai berdiskusi dengan tatap maya bersama peserta didik menggunakan Google Meet dengan mendiskusikan materi pembelajaran. Dari hasil penelitian tersebut dapat dilihat peningkatan hasil belajar matematika siswa pada nilai pretest sebelum memanfaatkan Google Workspace dengan nilai posttest setelah memanfaatkan Google Workspace. Google Workspace juga dapat mewujudkan pembelajaran berbasis digital, siswa lebih tertarik karena bisa belajar dimanapun dan kapanpun berada. Guru juga lebih mudah dalam penyampaian segala informasi dan penyimpanan dokumen pembelajaran.